STRATEGIES ADOPTED BY YAM FARMERS IN COMBATING CLIMATE CHANGE IN KOGI STATE NIGERIA - Sunday OGUNJIMI; Nancy IKEFUSI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Climate change has always been a thing of concern in agricultural production, especially in yam production. The study investigated farmer adaptation strategies to the effect of climate change on yam production in Kogi State with the specific objectives of assessing the socio-economic characteristics of farmers, farmers’ climate related constraints, the adaptation strategies employed by farmers, and yam farmers’ level of knowledge on climate change. A multistage sampling technique was used to select one hundred and twenty respondents from the different communities selected in the study area in year 2019. Data were collected through structured interview schedule. The data were analysed using frequency counts, percentages and Pearson Product Moment Correlation. Results obtained showed that farmers in the study area were mostly males with a mean age of 44.5 years. Most of the yam farmers in Kogi State got information on climate change from other farmers (77.3%) and (81.3%) of the respondents aware of climate change. Furthermore, the major effects of climate change as identified by the respondents were pest infestation (90.8%) and high rate weed growth (88.3%). Various strategies adopted by yam farmers include mulching (Mean=5.0), intercropping yam with other crops (Mean=4.5), use of weather-resistant variety (Mean=4.1) and use of early maturing crop varieties (Mean=3.8). Pearson product moment correlation shows that there is a significant relationship between estimated annual (r = 0.887), income farming experience (r = 0.274) and the farmers’ level of awareness. Therefore, efforts should be made towards developing and making available, yam seeds and yam tubers that can adapt to the change in climate and weather elements like flood and drought. These findings suggest the need for more training on climate change, the adaptation methods, environmental education and sustainability of yam cropping.